Local leakage current behaviours of BiFeO3 films - 邹成 陈斌 朱小健 左正笏 刘宜伟 陈远富 詹清峰 李润伟 (Chinese physics B, 2011)
The leakage current behaviours of polycrystalline BiFeO3 thin films are investigated by using both conductive atomic force microscopy and current-voltage characteristic measurements. The local charge transport pathways are found to be located mainly at the grain boundaries of the films. The leakage current density can be tuned by changing the post-annealing temperature, the annealing time, the bias voltage and the light illumination, which can be used to improve the performances of the ferroelectric devices based on the BiFeOa films. A possible leakage mechanism is proposed to interpret the charge transports in the polycrystalline BiFeO3 films.